(untitled) (Colloquia Comparativa Litterarum, 2025)
Verbal language is one of many theatrical languages, and it accounts for the spectators’ unhindered reception when one of the roles is performed in a foreign language. Andrea Fian and Maria Strozzi were two Croatian actors who acted upon the stage of Slavyanska Beseda Theatre (1904, 1905). Sofia Zvonareva was another guest actress from Croatia, and she was invited to stay for a couple of seasons as part of a Bulgarian troupe. Joseph Shmaha, a Czech actor and producer who was offered a position as artistic director at the Bulgarian National Theatre, also had two acting appearances on the Bulgarian stage. All guest actors, with the exception of Zvonareva, performed their roles in their native language even though the plays were staged in Bulgarian. This text shows the theatre critics’ attitude to the bilingual performances on the Bulgarian stage during the first decade of the 20th century, when Bulgarian professional theatre was making its first steps to develop purposefully as a national cultural institution.